Analisis Pertimbangan Hakim Dalam Sengketa Polis Asuransi Bank Pembiayaan Rakyat Syariah (Studi Kasus Putusan Nomor 0332/PDT.G/2019/PA.SGLT) - Ferdinan, Josua; Salsabila, Zhafirah; Putri, Fahda; Tarina, Dwi Desi Yayi (Media Hukum Indonesia (MHI), 2025)
Murabahah insurance is one of the main contracts carried out by Islamic banking, which is used to finance various customer needs, such as asset purchases, business financing, and others. In this case, there was a sharia economic dispute case at the Sungailiat Religious Court involving the Al-Murabahah financing agreement by the customer with PT Bangka Belitung Sharia People's Financing Bank (Defendant I), as well as the involvement of PT Jiwasraya Insurance (Defendant II) in providing credit life insurance. The purpose of the research in writing this article is to find out whether the Defendant is proven to have committed PMH seeing the existence of an unclear clause related to diseases that can disburse claims. The results of the analysis stated that Defendant II as having received premium payments and issued policies, but Defendant II rejected the claims submitted. So in this case Defendant II has committed a tortious act and must be responsible for the loss of customers.